Genetic insight into Nigerian population groups using an X-chromosome decaplex system. Issue 1 (December 2019) - Gomes, C.; Amorim, A.; Okolie, V.O.; Keshinro, S.O.; Starke, A.; Vullo, C.; Gusmão, L; Gomes, I
Abstract: African populations have higher genetic diversity representing an interesting continent for population genetic studies. A sample set from Nigeria, a West African country on the Gulf of Guinea, was genetically characterized using 10 X chromosomal short tandem repeat polymorphisms (DXS8378, DXS9898, DXS7133, GATA31E08, GATA172D05, DXS7423, DXS6809, DXS7132, DXS9902 and DXS6789). 218 unrelated male individuals belonging to three of the largest ethnic groups of Nigeria, namely Igbo, Hausa and Yoruba were sampled. No evidence for statistically significant LD (p ≤ 0.0011) between all pairs of markers was detected, which may be due to the low power of an exact test in small sample sizes. When studying the genetic affinity among the three studied ethnic groups, no significant differences were detected (FST ≤ 0.0069; p ≥ 0.045) which supports genetic homogeneity among the Nigerian groups for the studied X-chromosome decaplex markers. Parameters for forensic evaluation were also calculated demonstrating the potential application of these markers in diverse kinship scenarios in Nigeria where X-STR analyses may add value.